Excess returns on net foreign assets: the exorbitant privilege from a global perspective - Maurizio Michael Habib (European Central Bank (ECB), 2010)
This paper studies net foreign assets and the differential returns between gross foreign assets and liabilities for a sample of 49 countries between 1981 and 2007. It shows that investment income is more important than capital gains in imparting a drift to net foreign assets over the long-run, whereas the latter dominate short-term dynamics. Excess returns on net foreign assets of the United States are indeed exorbitant from a global perspective, only occasionally matched by other countries and mainly accounted for by positive valuation effects. The role of the United States as levered investor did not contribute to its exorbitant privilege. The econometric panel analysis also fails to find a robust positive relationship between leverage and excess returns. Notably, instead, real exchange rate depreciations increase excess returns through capital gains, proportionally to the relative foreign currency exposure. Excess yields on investment income are positively associated with the country risk rating.
Keywords: F30; F31; F36; 330; excess returns; exorbitant privilege; leverage; net foreign assets; Auslandsvermögen; Kapitaleinkommen; Panel; USA; Welt